Service-state austenitic stainless steel metallographic corrosive agent and metallographic structure display method
By using corrosion agents composed of copper sulfate, sodium metabisulfite, etc., combined with sandpaper grinding and mechanical polishing, the problems of over-invasion and excessive corrosion in the detection of existing austenitic stainless steel metallographic corrosion agents have been solved, and the grain boundaries and The effect of the phase precipitation in the crystal improves detection efficiency and safety, and is suitable for austenitic stainless steel running at high temperature and high pressure.
Patent Information
- Application Number
- CN202411298862.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
AI Technical Summary
The existing austenitic stainless steel metallographic corrosion agents have over-invasion and too light corrosion during detection, making it difficult to clearly display the grain boundaries and intra-crystal phases, and the safety and detection efficiency are low, especially not suitable for high-temperature and high-pressure operation. Austenitic stainless steel and fine-grained austenitic stainless steel.
Provided is a corrosion agent composed of copper sulfate, sodium metabisulfite, sodium dodecylbenzenesulfonate, hexadecimal methyltetramine and diluted concentrated hydrochloric acid. It is prepared by specific ratios and preparation methods, combined with sandpaper grinding and Mechanical polishing treatment, control the erosion time, and use degreased cotton balls to dip the corrosion agent for local wipe.
This corrosive agent can clearly display the austenite grain boundary and σ phase, M23C6 and other harmful aging precipitation phases, with high stability and 8 times more detection efficiency. It is suitable for metallographic structure evaluation of large-scale austenite stainless steel, with high safety and suitable In a high temperature and closed environment on site.
Smart Images

Figure CN119124781A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metallographic etching agent for austenitic stainless steel in service state and a metallographic structure display method, belonging to the technical field of metallographic inspection. Background Art
[0002] Metallographic testing is a method for testing the properties of metal materials. Compared with low-alloy pipes, austenitic stainless steel is not easily corroded and is easily affected by the concentration of the corrosive agent and the sample preparation effect. Commonly used corrosive agents such as aqua regia and hydrochloric acid FeCl3 aqueous solution are not effective in laboratory and on-site metallographic corrosion. The corrosion rate of aqua regia is too fast. If it is applied to austenitic stainless steel that is operated at high temperature and high pressure for a long time, it is prone to over-corrosion. The corrosion ability of hydrochloric acid FeCl3 aqueous solution is weaker than that of aqua regia. Although the austenite grain boundary display effect is better, it has a poor effect on the carbides precipitated inside the austenite grains and on the grain boundaries. 23 The display effect of C6 and σ phase is not good, and the dirt produced during the etching process is easy to adhere to the surface of the metallographic sample and is not easy to rinse clean, which is not conducive to the observation of the metallographic structure.
[0003] Chinese invention patent CN101353794A discloses an austenitic stainless steel metallographic etching agent and its preparation method and application. The metallographic etching agent is a mixed solution of hydrofluoric acid and nitric acid, and the proportions of the components are: hydrofluoric acid: nitric acid: water = 2: 1: 7. The etching time of the reagent is 20 to 60 minutes, and the weak etching ability leads to a long etching time, which is not conducive to large-scale rapid detection. In addition, the high content of hydrofluoric acid will seriously endanger the health of testers. At the same time, the reagent is not suitable for metallographic detection of 18-8 type chromium-nickel austenitic stainless steel for boiler heating surface pipes.
[0004] Chinese invention patent CN116103654A discloses an etchant that can be used for on-site austenitic metallographic structure inspection and evaluation. Although this etchant can clearly display the σ phase and grain boundaries in austenitic stainless steel, there is a certain over-invasion phenomenon at the grain boundaries. The ratio of hydrogen peroxide solution to ethanol solution needs to be controlled. Hydrogen peroxide is a strong oxidant. The preparation process will cause certain harm to human health. At the same time, a surfactant component is required, and the cost is relatively high. At the same time, in actual use, it is found that it is not suitable for fine-grained austenitic stainless steels such as TP347HFG, and the effect described in the patent cannot be achieved after corrosion. Therefore, it is necessary to develop an etchant that is easy to mix on-site, has a wider range of applications, and has a solvent that is easier to obtain safely, so as to improve the efficiency and safety of the detection of austenitic stainless steel boiler pipelines in service with different degrees of aging. Summary of the invention
[0005] In order to improve the efficiency and accuracy of metallographic structure detection of austenitic stainless steel in power plants, the present invention aims to provide a metallographic structure display method for austenitic stainless steel in different service states, which can clearly display austenite grain boundaries and σ phase, M phase, 23 Harmful aging precipitation phases such as C6 are easy for testers to distinguish, and have the advantages of strong stability, high detection efficiency, and high safety. It is suitable for on-site organization assessment of large quantities of austenitic stainless steel pipes for (super)critical boilers, significantly improving the efficiency of power plant maintenance and troubleshooting.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the present invention is, on the one hand, to provide a metallographic etching agent for austenitic stainless steel in service state, comprising the following raw materials: 1g copper sulfate, 1g sodium pyrosulfite, 1.5g sodium dodecylbenzene sulfonate, 1.5g hexamethylenetetramine, 8-12ml concentrated hydrochloric acid, and 35-40ml deionized water.
[0007] Furthermore, the mass fraction of the concentrated hydrochloric acid is 36-38%.
[0008] On the other hand, the technical solution of the present invention is to provide a method for preparing the corrosive agent, dissolving all solid raw materials except concentrated hydrochloric acid in deionized water, then adding concentrated hydrochloric acid, and standing for more than 1 hour to obtain a metallographic corrosive agent for austenitic stainless steel in service state.
[0009] On the other hand, the technical solution of the present invention is to provide a method for displaying the metallographic structure of austenitic stainless steel in service state, using sandpaper of different mesh sizes to grind the surface of the sample, and then mechanically polishing it. After polishing, wipe off the oil stains on the polished surface with a cotton ball sprayed with alcohol; then wipe the surface of the metallographic sample with an absorbent cotton ball dipped in the corrosive agent, and control the total corrosion time to be 10 to 40 seconds until the polished surface detection surface is uniformly gray; spray the eroded surface with alcohol, and then gently wipe off the residual alcohol and dust on the surface with a cotton ball; finally, use metallographic detection equipment to detect it.
[0010] Furthermore, the grit of the sandpaper is 400, 600, and 1000.
[0011] Furthermore, before polishing, a polishing paste is applied to the surface of the sample, and the particle size of the polishing paste is 2.5 to 5.0 μm.
[0012] On the other hand, the technical solution of the present invention is to provide an application of the corrosive agent in detecting the aging condition and grain size of the metallographic structure of austenitic stainless steel in service.
[0013] Compared with the prior art, the present invention has the following advantages:
[0014] (1) The etchant of the present invention has a good adaptability to austenite structures of different service levels, making it easier to grasp the corrosion time and the structure after corrosion, and it is not easy to have excessive corrosion or too light corrosion. At the same time, the grain boundary, intragranular and grain boundary precipitation phases, especially the σ phase (pure white under an optical microscope) can be clearly displayed, and the inspector can easily obtain key information such as grain size level and structure aging level.
[0015] (2) The etchant prepared by the present invention is stable, suitable for high-temperature closed environments on site, and easy to operate. The etchant can be directly wiped with an absorbent cotton ball dipped in the reagent at the metallographic polishing point to achieve the effect of completely corroding and revealing the local tissue morphology. Even if it is stored for a long time after preparation, the effect of the etchant of the present invention will not be reduced, and it still has a good corrosion effect.
[0016] (3) The etchant of the present invention is simple and cheap to prepare, and the raw materials used are safe. The acid reagent used is a diluted hydrochloric acid solution, which does not contain some strong oxidizing agents. If it accidentally touches the skin during the erosion process, it can be immediately washed with water or alcohol. The risk of use is small and basically does not cause damage to the skin. At the same time, the on-site detection efficiency is high, which is suitable for the large aging degree and grain size inspection of austenitic stainless steel in large quantities on site. When used on site, a single group of metallographic inspection personnel can detect more than 150 metallographic points within an effective working time of 7 hours on average, and the detection efficiency is improved by more than 8 times. When a power plant was conducting a metallographic inspection of four boiler pipes, two groups of personnel used the etchant of the present invention to complete the metallographic inspection of about 2,100 points on site in 7 days. It was found that the grain size of about 35% of the metallographic measurement points did not meet the standard requirements, about 3.1% had moderate aging of level 3 or above, and about 2.5% had severe aging of level 5 or above. The detection results provide convenience for the power plant to timely understand the operating status of the unit and formulate maintenance measures, shorten the maintenance time of the power plant, and improve production and economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a metallographic photograph of a moderately aged sample of TP304H steel tested by a corrosive agent in Example 1.
[0018] Figure 2 This is a metallographic photograph of a severely aged sample of TP304H steel tested by a corrosive agent in Example 1.
[0019] Figure 3 This is a metallographic photograph of a moderately aged sample of Super304H steel tested by a corrosive agent in Example 2.
[0020] Figure 4 This is a metallographic photograph of a severely aged sample of Super304H steel tested with a corrosive agent in Example 2.
[0021] Figure 5This is a metallographic photograph of a moderately aged sample of HR3C steel tested by the corrosive agent in Example 3.
[0022] Figure 6 This is a metallographic photograph of a severely aged sample of HR3C steel tested by the corrosive agent in Example 3.
[0023] Figure 7 This is a metallographic photograph of a moderately aged sample of TP347H steel tested by a corrosive agent in Example 1.
[0024] Figure 8 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested by a corrosive agent in Example 1.
[0025] Fig. 9 This is a metallographic photograph of a moderately aged sample of TP347H steel tested by a corrosive agent in Comparative Example 1.
[0026] Fig.10 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested by a corrosive agent in Comparative Example 1.
[0027] Fig.11 This is a metallographic photograph of a moderately aged sample of TP347H steel tested with a corrosive in comparative example 2.
[0028] Fig.12 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested with a corrosive agent in comparative example 2.
[0029] Fig.13 This is a metallographic photograph of a moderately aged sample of TP347H steel tested with the corrosive agent in comparative example 3.
[0030] Fig.14 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested with the corrosive agent in comparative example 3.
[0031] Fig.15 This is a metallographic photograph of a moderately aged sample of TP347H steel tested with the corrosive agent in comparative example 4.
[0032] Fig.16 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested with a corrosive in comparative example 4.
[0033] Fig.17 This is a metallographic photograph of a moderately aged sample of TP347H steel tested with the corrosive agent in comparative example 5.
[0034] Fig.18 This is a metallographic photograph of a severely aged sample of TP347HFG steel tested with the corrosive agent in comparative example 5. DETAILED DESCRIPTION
[0035] The specific implementation modes of the present invention are further described in detail below in conjunction with the embodiments.
[0036] Example 1
[0037] A metallographic etching agent for austenitic stainless steel in service state comprises the following raw materials: 1g of copper sulfate, 1g of sodium pyrosulfite, 1.5g of sodium dodecylbenzene sulfonate, 1.5g of hexamethylenetetramine, 8ml of concentrated hydrochloric acid (mass fraction 36-38%) and 35ml of deionized water.
[0038] Figure 1 and 2 The metallographic structure photographs of the moderately aged sample and the severely aged sample of TP304H steel grade detected by the corrosive agent in Example 1. Metallographic structure display method: First, use sandpaper with different mesh sizes to grind the sample surface, and the sandpaper mesh sizes are 400, 600, and 1000; then perform mechanical polishing, and apply oily diamond powder polishing paste to the sample surface before polishing, and the particle size of the polishing paste is 2.5-5.0μm; after polishing at the metallographic detection point, wipe off the surface oil with a cotton ball sprayed with alcohol; then dip an appropriate amount of corrosive into an absorbent cotton ball and wipe the surface of the metallographic sample, controlling the total corrosion time to 10-40 seconds, until the polished detection surface is uniformly gray; spray the eroded surface with alcohol, and then use a cotton ball to gently wipe off the residual alcohol and dust on the surface; finally, use metallographic detection equipment for detection. By Figure 1 and 2 It can be seen that the corrosion effect of the corrosive agent in Example 1 on the moderately aged sample of TP304H steel is that the grain boundaries are clear and the precipitated phases at the grain boundaries are clearly visible. The corrosion effect on the severely aged sample is that the grain boundaries are clear and the aged precipitated phases in the grains and at the grain boundaries are clearly visible.
[0039] Example 2
[0040] A metallographic etching agent for austenitic stainless steel in service state comprises the following raw materials: 1g of copper sulfate, 1g of sodium pyrosulfite, 1.5g of sodium dodecylbenzene sulfonate, 1.5g of hexamethylenetetramine, 12ml of concentrated hydrochloric acid (mass fraction 36-38%) and 40ml of deionized water.
[0041] Figure 3 and 4The metallographic structure photographs of the moderately aged and severely aged samples of Super304H steel grade detected by the corrosive agent in Example 2. Metallographic structure display method: First, use sandpaper with different mesh sizes to grind the sample surface, and the sandpaper mesh sizes are 400, 600, and 1000; then perform mechanical polishing, and apply oily diamond powder polishing paste to the sample surface before polishing, and the particle size of the polishing paste is 2.5-5.0μm; after polishing at the metallographic detection point, wipe off the surface oil with a cotton ball sprayed with alcohol; then dip an absorbent cotton ball in an appropriate amount of corrosive and wipe the surface of the metallographic sample, controlling the total corrosion time to 10-40 seconds, until the polished detection surface is uniformly gray; spray the eroded surface with alcohol, and then use a cotton ball to gently wipe off the residual alcohol and dust on the surface; finally, use metallographic detection equipment for detection. By Figure 3 and 4 It can be seen that the corrosion effect of the corrosive agent in Example 2 on the moderately aged sample of Super304H steel is that the grain boundaries are clear and the precipitated phases at the grain boundaries are clearly visible. The corrosion effect on the severely aged sample is that the grain boundaries are clear and the aged precipitated phases in the grains and at the grain boundaries are clearly visible.
[0042] Example 3
[0043] A metallographic etching agent for austenitic stainless steel in service state comprises the following raw materials: 1g of copper sulfate, 1g of sodium pyrosulfite, 1.5g of sodium dodecylbenzene sulfonate, 1.5g of hexamethylenetetramine, 10ml of concentrated hydrochloric acid (mass fraction 36-38%) and 38ml of deionized water.
[0044] Figure 5 and 6 The metallographic structure photographs of the moderately aged and severely aged samples of HR3C steel grade detected by the corrosive agent of Example 3. Metallographic structure display method: First, use sandpaper of different mesh sizes to grind the surface of the sample, and the sandpaper mesh sizes are 400, 600, and 1000; then perform mechanical polishing, and apply oily diamond powder polishing paste to the surface of the sample before polishing, and the particle size of the polishing paste is 2.5-5.0μm; after polishing at the metallographic detection point, wipe off the surface oil with a cotton ball sprayed with alcohol; then dip an appropriate amount of corrosive into an absorbent cotton ball and wipe the surface of the metallographic sample, controlling the total corrosion time to 10-40 seconds, until the polished detection surface is uniformly gray; spray the eroded surface with alcohol, and then use a cotton ball to gently wipe off the residual alcohol and dust on the surface; finally, use metallographic detection equipment for detection. By Figure 5 and 6 It can be seen that the corrosion effect of the etchant in Example 3 on the moderately aged sample of HR3C steel is that the grain boundaries are clear and the precipitates gathered at the grain boundaries can be clearly observed. The corrosion effect on the severely aged sample is that the grain boundaries are still relatively clear and the aged precipitates in the grains and at the grain boundaries are more easily observed.
[0045] Comparative Example 1
[0046] DL / T884-2019 conventional corrosive agent, including the following raw materials: 4g copper sulfate, 20ml hydrochloric acid, 20ml water.
[0047] Comparative Example 2
[0048] The corrosive agent in CN116103654A "A metallographic corrosive agent for austenitic stainless steel, its preparation method and application" by Rundian Energy Science and Technology Co., Ltd. includes the following raw materials: 1g of ferric chloride, 2g of ammonium persulfate, 10ml of concentrated hydrochloric acid (mass fraction 36-38%), and 100ml of hydrogen peroxide ethanol solution (the volume of hydrogen peroxide is 50% of the total volume of the hydrogen peroxide ethanol solution).
[0049] Comparative Example 3
[0050] The etchant is substantially the same as that in Example 1, except that the etchant in this comparative example uses an equal amount of potassium permanganate to replace sodium pyrosulfite.
[0051] Comparative Example 4
[0052] The etchant is substantially the same as that in Example 1, except that the etchant in this comparative example uses an equal amount of ferric chloride to replace copper sulfate.
[0053] Comparative Example 5
[0054] The etchant is substantially the same as that in Example 1, except that the etchant in this comparative example uses an equal amount of alcohol (mass fraction 99.7%) to replace deionized water.
[0055] To further verify the corrosion effect of the etchant of the present invention, the etchant prepared in Example 1 and Comparative Examples 1-5 was used to detect the metallographic structure of the same service-state austenitic stainless steel material. The austenitic stainless steel materials used in the test: moderately aged sample: TP347H steel; severely aged sample: TP347HFG steel.
[0056] Metallographic structure display method: first, use sandpaper with different meshes to grind the sample surface, and the sandpaper meshes are 400, 600, and 1000; then perform mechanical polishing, and apply oily diamond powder polishing paste on the sample surface before polishing, and the particle size of the polishing paste is 2.5-5.0μm; after polishing at the metallographic detection point, wipe off the surface oil with a cotton ball sprayed with alcohol; then dip an appropriate amount of corrosive with an absorbent cotton ball and wipe the surface of the metallographic sample, and control the total corrosion time to 10-40 seconds until the polished surface is uniformly gray; spray the eroded surface with alcohol, and then use a cotton ball to gently wipe off the residual alcohol and dust on the surface; finally, use metallographic detection equipment to detect and compare the corrosives prepared by different methods on the display effect of medium / severe aging structure of austenitic stainless steel, and the results are as follows.
[0057] The etching solution prepared in Example 1 of the present invention has a good etching effect. Figure 7 As shown in Figure 1, under an optical microscope, the grain boundaries and the precipitation phases in the grains are clearly visible for the moderately aged sample. Figure 8 As shown, the common σ phase, M 23 The C6 precipitated phases are all pure white, with clear grain boundaries, no impurities in the grains, and high recognition. Therefore, the overall effect is better than the existing related detection reagents, and further improves the efficiency of testers in obtaining key information such as grain size and aging level based on tissue photos.
[0058] Fig. 9 and 10 The results show that the corrosion effect of the etchant provided by the DL / T884-2019 standard in Comparative Example 1 on the moderately aged sample can clearly display the grain boundary and the intragranular precipitation phase. The corrosion effect on the severely aged sample can clearly display the grain boundary, but the σ phase and M phase are not visible. 23 The C6 precipitation phase has poor effect.
[0059] Fig.11 and 12 The results show that the corrosion effect of the etchant provided by CN116103654A in Comparative Example 2 on the moderately aged sample is that the amount of intracrystalline precipitated phase is small and the display effect is not good. However, the white blocky σ phase and M phase can be clearly displayed on the severely aged sample. 23 C6 precipitates, but the grain boundary display effect is poor.
[0060] Fig.13 and 14 The corrosion effect of replacing the sodium pyrosulfite with an equal amount of potassium permanganate in comparative example 3 can be observed. Fig.13 and 14 There is a phenomenon of excessive tissue erosion, and the display effects of grain boundaries and intra-grain are poor.
[0061] Fig.15 and 16 The corrosion effect of the etchant using the same amount of ferric chloride instead of copper sulfate in Comparative Example 4 can be observed. Fig.15 and 16 The degree of tissue erosion is relatively mild. Fig.15 The grain boundaries of the moderately aged samples in the middle are lightly displayed, some grain boundaries are disconnected, the distribution of grain boundary precipitates is uneven, the amount of precipitated phases in the grains is small, and the display effect is not good. Fig.16 Although the severely aged sample can clearly show white blocky σ phase and M 23 C6 precipitates, but the grain boundary display effect is poor.
[0062] Fig.17 and 18The corrosion effect of the etchant in comparative example 5, in which the deionized water is replaced by an equal amount of alcohol, can be observed. Fig.17 and 18 The degree of tissue erosion is mild. Fig.17 The grain boundaries of the moderately aged samples in the figure are not fully displayed, the amount of precipitated phases in the grains is very small, and the display effect is poor. Fig.18 Although the severely aged samples in the experiment can show white blocky σ phase and M 23 C6 precipitates, but the grain boundary display effect is poor.
Claims
1. A metallographic etchant for austenitic stainless steel in service, characterized in that: The method comprises the following raw materials: 1 g of copper sulfate, 1 g of sodium pyrosulfite, 1.5 g of sodium dodecylbenzene sulfonate, 1.5 g of hexamethylenetetramine, 8 to 12 ml of concentrated hydrochloric acid, and 35 to 40 ml of deionized water.
2. The etchant according to claim 1, characterized in that The raw materials include: 1 g copper sulfate, 1 g sodium metabisulfite, 1.5 g sodium dodecylbenzene sulfonate, 1.5 g hexamethylenetetramine, 8 ml concentrated hydrochloric acid, and 35 ml deionized water.
3. The etchant according to claim 1, characterized in that The raw materials include: 1 g copper sulfate, 1 g sodium metabisulfite, 1.5 g sodium dodecylbenzene sulfonate, 1.5 g hexamethylenetetramine, 12 ml concentrated hydrochloric acid, and 40 ml deionized water.
4. The etchant according to claim 1, characterized in that The raw materials include: 1 g copper sulfate, 1 g sodium metabisulfite, 1.5 g sodium dodecylbenzene sulfonate, 1.5 g hexamethylenetetramine, 10 ml concentrated hydrochloric acid, and 38 ml deionized water.
5. The etchant according to any one of claims 1 to 4, characterized in that: The mass fraction of the concentrated hydrochloric acid is 36-38%.
6. A method for preparing the etchant according to any one of claims 1 to 4, characterized in that: All solid raw materials except concentrated hydrochloric acid are dissolved in deionized water, and then concentrated hydrochloric acid is added and allowed to stand for more than 1 hour to prepare a metallographic etching agent for austenitic stainless steel in service state.
7. A method for displaying the metallographic structure of austenitic stainless steel in service state, characterized in that: The sample surface is grinded with sandpaper of different meshes, and then mechanically polished. After polishing, the oil stain on the polished surface is wiped off with a cotton ball sprayed with alcohol; then, an absorbent cotton ball is dipped in the corrosive agent described in any one of claims 1 to 4 and then wiped on the surface of the metallographic sample, and the total erosion time is controlled within 10 to 40 seconds, until the polished surface is uniformly gray; the eroded surface is sprayed with alcohol, and then the residual alcohol and dust on the surface are gently wiped off with a cotton ball; finally, the metallographic detection equipment is used for detection.
8. The metallographic structure display method according to claim 7, characterized in that: The grit of sandpaper is 400, 600 and 1000.
9. The metallographic structure display method according to claim 7, characterized in that: Before polishing, apply polishing paste on the surface of the sample, and the particle size of the polishing paste is 2.5 to 5.0 μm.
10. Use of the corrosive agent according to any one of claims 1 to 4 in detecting the aging of the metallographic structure and the grain size of austenitic stainless steel in service.
